A Review: eco-friendly technologies and sustainable development of urban friendliness spaces toward new urbanism design approach - Omar Abdul wahhab Khalaf; Nor Haslina Ja`afar; Mohd Iskandar Abd Malek; Elina Mohd Husini (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ecologically conscious technology is a fast-developing domain centring around novel scientific and technical approaches that bring advantages to the planet. Commonly known as “sustainable technology”, this field is committed to conserving our natural resources. Therefore, urban Friendliness spaces are essential to all users as it stands as a public space which provides a sustainable environment for a more walkable, safe, and green environment. The problem statement of this study is imperative to enhance the sustainability and eco-friendliness of urban Friendliness spaces. Thus, this paper aims to incorporate both the development of new technologies and the improvement of existing ones to physically and functionally enhance the Friendliness spaces. The methodology involved a systematic literature review of new urbanism design approaches, which was achieved through a structured review of existing literature. Our results indicate that many key design elements, inventions, improvements, and scientific developments can have an impact on the ecosystem of urban spaces, subsequently affecting the people on an individual level. The findings of this study hope to contribute to the body of knowledge on how to improve urban development toward producing an eco-friendly and sustainable built environment.